Jeu vidéo et science-fiction >> de mode texte en code texte - Estelle Dalleu (ReS Futurae)
The science-fiction issue is relatively unaddressed in the field of video game studies, as if it was obvious that to showing science put into fiction echoed what the video game is intrinsically : technologies set on test by fictional worlds - and vice versa. Video games and science-fiction, however, have unique links, for example in representations based entirely on the text mode. As both a narrative and a gameplay tool, the text mode consists in its essence in a mise-en-abyme : the player is set in front of a textual feedback that installs them in a scriptural dialogue with a computer. What the playable character does in game is nothing else than what players do themselves, that is to say interacting with a machine — an entity with which a connection is developed which lays the foundations of the science-fiction construction of the video game. The text mode, present from the first video game experiences, and which continues in the most contemporary video games, paves the way to what works deeply in the relationship between the human and the computer machine : the artificial intelligence.